Jawabanmu

2014-01-27T17:40:39+07:00
U1 = a = 3

U6 + U7 = 9
[a + (6-1)b] + [a + (7-1)b] = 9
[3 + 5b] + [3 + 6b] = 9
6 + 11b = 9
11 b = 9 - 6
11b = 3
b =  \frac{11}{3}




Un= 87
a + (n-1)b = 87
3 + (n-1)
 \frac{11}{3} = 87
3 +  \frac{3}{11} n -  \frac{3}{11} = 87
 \frac{36}{11} +  \frac{3}{11} n = 87
 \frac{3}{11} n = 87 -  \frac{36}{11}
 \frac{3}{11} n =  \frac{957}{11}
3n = 957
n = 319


U50 = 3 + 49b
       = 3 + 49  \frac{3}{11}
       = 3 + 13,3
       = 16,3



semoga membantu :)






1 5 1